2001
DOI: 10.1095/biolreprod65.3.660
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the Adult Leydig Cell Population in the Postnatal Testis1

Abstract: Five main cell types are present in the Leydig cell lineage, namely the mesenchymal precursor cells, progenitor cells, newly formed adult Leydig cells, immature Leydig cells, and mature Leydig cells. Peritubular mesenchymal cells are the precursors to Leydig cells at the onset of Leydig cell differentiation in the prepubertal rat as well as in the adult rat during repopulation of the testis interstitium after ethane dimethane sulfonate (EDS) treatment. Leydig cell differentiation cannot be viewed as a simple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
164
2
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(185 citation statements)
references
References 125 publications
13
164
2
6
Order By: Relevance
“…It is generally accepted that in mature males, the number of Leydig cells is kept constant and, thus, does not explain changes of the testis size as also found in the present study (Mendis-Handagama and Ariyaratne, 2001).…”
Section: 6contrasting
confidence: 39%
“…It is generally accepted that in mature males, the number of Leydig cells is kept constant and, thus, does not explain changes of the testis size as also found in the present study (Mendis-Handagama and Ariyaratne, 2001).…”
Section: 6contrasting
confidence: 39%
“…The Sertoli cells and Leydig cells are extremely important in this process. Additionally, Sertoli cells are responsible for supporting and nourishing the germ cells, releasing spermatozoa into the lumen, while Leydig cells boost libido and maintain spermatogenesis (Bilaspuri and Guraya 1986;Benton et al 1995;Chamindrani Mendis-Handagama and Siril Ariyaratne 2001;França et al 2005;Gendt et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized, but far from proven, that LCs first arise from undifferentiated stem cells [stem LCs (SLCs)] (1-3). It has been suggested that, in rats, the putative SLCs are present in the testis at birth, and that by 11 days postpartum, at least some of their progeny express LC-specific genes and thus become committed to the LC lineage (4,5).…”
mentioning
confidence: 99%
“…PDGFR␣ also appears in situ during the first week postpartum in the interstitial spindle-shaped cells that are putative SLCs (11), when neither 3␤HSD nor LHR is detected in these cells (1,4). Analyses of PLCs, ILCs, and ALCs make it evident that testicular PDGFR␣ expression is restricted to the LC lineage (6,12).…”
mentioning
confidence: 99%